Epidemiology of Sub-Clinical Mastitis in Dairy Cows in Urban Areas of Chittagong, Bangladesh - Shariful Islam (Turkish Journal of Agriculture: Food Science and Technology, 2019)
Mastitis is considered to be the most devastating condition for the dairy farms of low and medium income countries due to its alarming impact on production and worldwide has been recognized as one of the most economically significant infectious diseases affecting the welfare of dairy animal. Chittagong is one of the dairy intensive regions of Bangladesh but comprehensive epidemiological studies addressing prevalence of and risk factors for subclinical mastitis (SCM) are scant. Therefore we aimed to approximate the prevalence of SCM in dairy cows along with the associated risk factors in dairy cows of Chittagong Metropolitan Area (CMA), Bangladesh. We included 114 cross breed (Holstein × Local) lactating cows, raised at 6 dairy farms in CMA between February to November, 2015 for this study. California Mastitis Test (CMT) was used to assess SCM at animal level. The overall prevalence of mastitis was 34.2% among the tested cows. Floor type, source of replacement cows, history of previous reproductive disorder, stage of lactation and cleanliness of floor was found significantly associated with SCM in univariate analysis. In random effect multiple logistic regression model, cemented floor was found to increase the odds of SCM by 5.03 times than that of brick floor. Similarly, cows with history of reproductive disorders had more risk of having SCM than that of cows without a history of reproductive disorders. Since the SCM is prevalent in the study area, the intervention strategy should focus on causal agent, improved management, frequent monitoring of SCM in milking cows with CMT and use of teat disinfectants; with minimal or no treatment with antimicrobial agents.